A new Concentrated Photovoltaic Thermal-Hydrogen system with photocatalyst suspension as optical liquid filter. (July 2022) - Ma, Ben-Chi; Lin, Hua; Zhu, Yizhou; Zeng, Zilong; Geng, Jiafeng; Jing, Dengwei
Abstract: Although typical Concentrated Photovoltaic-Thermal systems can overcome high cell temperatures, the low-level heat generated not only increases the irreversible energy loss but also narrows the application scope of the system. Here, we established a new Concentrated Photovoltaic Thermal-Hydrogen system coupling the Pt loaded TiO2 nanoparticle suspension, serving as both a photothermal hydrogen catalyst and an optical liquid filter for spectrum beam splitting, with a GaInP/GaAs/Ge triple-junction photovoltaic cell connected to an electrolytic cell to achieve full-spectrum solar energy to hydrogen storage conversion. Besides the additional hydrogen production, the Concentrated Photovoltaic Thermal-Hydrogen system with spectral beam splitting of TiO2 suspension can reduce the cell temperature by 32.8%, increase the electrical power by 65.7%, and save 49% of the cell area at most, compared to the case without spectral beam splitting. Thermalization loss was also reduced, which, in turn, increased the photovoltaic electrical performance. The proposed system can produce hydrogen at a maximum solar-to-hydrogen efficiency of 14% when the TiO2 loading amount is 150 ppm. It is expected to provide a guiding reference for achieving full-spectrum and high-efficiency solar energy conversion. Graphical abstract: Image 1 Highlights: CPVT-H system can achieve full-spectrum STH efficiency of 14%. The system achieved lower PV temperature increase and power decrease. The Pt/TiO2 suspension acted both as an optical filter and a photocatalyst.